Exit exams design in higher education: A systematic review - Teshome, Samson Worku (Univeritas Papua, 2025)
This systematic literature review explores the design issues surrounding exit exams in higher education, focusing on their validity, reliability, and impact on student outcomes. As exit exams have become integral to assessing student competencies, the need for effective and equitable assessment strategies is paramount. The review synthesizes two decades of research to identify key challenges, including the alignment of exam content with educational objectives, the tension between standardization and customization, and the engagement of diverse stakeholders. The findings reveal that while exit exams are essential for ensuring graduates meet established competencies, they often face criticism due to concerns over fairness and the potential narrowing of curricula. The review underscores the importance of stakeholder perspectives, including those of faculty, students, and administrators, in shaping the design and implementation of exit exams. Furthermore, ethical considerations regarding the role of assessments in educational experiences are discussed. The review concludes with recommendations for a holistic approach to exit exam design, emphasizing collaboration among stakeholders and the need for ongoing training for faculty. Future research directions are also proposed, advocating for innovative assessment strategies and longitudinal studies to evaluate the long-term impacts of exit exams. By addressing these critical design issues, this review aims to contribute to the ongoing discourse in higher education assessment and promote student achievement and educational equity.